Cognitive task-related functional connectivity alterations in temporal lobe epilepsy - Strýček, Ondřej; Lamoš, Martin; Klimeš, Petr; Rektor, Ivan (Epilepsy & behavior, 2020)
OBJECTIVE: We investigated cognitive task-related functional connectivity (FC) in patients with temporal lobe epilepsy (TLE). Using a visual three-stimulus paradigm (VTSP), we studied cognitive large-scale networks and the impact of TLE on connectivity outside the temporal lobe. METHODS: High-density electroencephalography (EEG) was recorded during the paradigm from nineteen patients with epilepsy with hippocampal sclerosis (HS) and ten healthy controls (HCs). Scalp data were reconstructed into the source space, and FC was computed. Correlating with the neuropsychological data, possible compensatory mechanisms were investigated. RESULTS: Significant changes were found in the FC of regions outside the epileptogenic network, particularly in the attentional network. These changes were more widespread in left TLE (LTLE). There were no significant differences in task performance (accuracy, time response) in comparison with HCs, implying that there must be some mechanism reducing the impact of connectivity changes on brain functions. When correlated with neuropsychological data, we found stronger compensatory mechanisms in right TLE (RTLE). SIGNIFICANCE: Our findings confirm the hypothesis that LTLE is the more pervasive form of the disease. Even though the network alterations in TLE are severe, some mechanisms reduce the impact of epilepsy on cognitive functions; these mechanisms are more potent in RTLE. We also suggest that there are maladaptive mechanisms in LTLE.
Keywords: kognice; magnetická rezonanční tomografie; mapování mozku; Functional Laterality; Humans; lidé; funkční lateralita; Epilepsy, Temporal Lobe; epilepsie temporálního laloku; Temporal lobe epilepsy; Cognitive network; Magnetic Resonance Imaging; High-density EEG; Functional connectivity; Brain Mapping; Cognition